Infiltração bacteriana nas interfaces entre implantes e pilares: efeito do desenho das conexões protéticas - Lima, Elen Guerra de [UNESP] (2014)
The aim of this study was to evaluate the in vitro bacterial microleakage at the interface between the abutment and the implant, comparing 3 types of prosthetic connections: External Hexagon (EH), Internal Hexagon (IH), Taper Connection (TC), the latter of 3 different types of the design of the abutments. For this, it was utilized 150 sets (abutment / implant), that were divided into 5 groups (n = 30). G1 (Control) - EH abutments; G2 - IH abutments; G3 - TC solid abutments; G4 - TC indexed abutments; G5 - TC zero line abutments. For this evaluation, suspension of the bacterial Escherichia coli (ATCC 25922) e Streptococcus sanguinis (ATCC 10557) were inoculated in the apical portion of the abutment screw, under sterile conditions. The abutments were fixed to the implants and torqued according to manufacturer's recommendations, and immersed in sterile BHI broth for 14 days. At the end of the period all sets were separated, the inner contents was be sonicated, diluted, seeded and taken to a bacteriological incubator (37 °C for 24 hours) to check the viability of the bacteria. The samples that did not contain viable E. coli e S. sanguinis were discarded from the study. The staining and bacterial morphology were observed in optical microscope and scanning electron microscopy (SEM). Results of colony forming units (CFUs) were analyzed by ANOVA 1 factor. There were no differences between the percentage of bacterial infiltration for IH (9.09%), CS (21.74%), CI (22.73%) e C0 (11.11%). Analising separetly the groups non-infritated with E. coli (p = 0,126) and S. Sanguinis (p = 0,962) and the groups infiltrated with E. coli and S. sanguinis (p = 0,655.) (p < 0,05), there no was statistical difference in the count of CFU/ml between the connections type